The Queen's faithful companion : a novel of Queen Elizabeth II and her beloved corgi, Susan - Knight, Eliza (William Morrow, an imprint of HarperCollins Publishers, 2024)
Elizabeth wasn’t born to be queen. But when her uncle abdicates and her father steps in as king, everything in her life changes. There is one thing that never wavers, however: her endearing love of her Corgis--especially the new puppy Susan, a gift for her eighteenth birthday. Susan is by her side during Elizabeth’s WWII service, falling in love with Philip and getting married, the death of her father King George VI, her accession to the throne, the birth of her first child, and the early struggles with running a country--an ever-present reminder to find the balance between self and crown. A loyal servant…Hanna Penwyck has grown up with her family in service to the crown. Awkward and shy, she has a connection with nature, animals--and the young princesses at Windsor. When she becomes the Keeper of the Queen’s Corgis, her job is to maintain the health and wellness of those most prized companions. With their shared love of the dogs, the Queen can open up to Hanna and feel free to be herself, so that is a service she happily provides as well. A faithful companion…From the moment Susan became a royal dog, her duty was clear: To remind Elizabeth that she is more than just a queen, she is a human, and what matters is not just duty and honor, but connection, family, and unconditional and enduring love. Susan is the keeper of memories, of secrets. Through Susan we gain a dog’s eye view of royal life, human relationships, and the heartwarming bond between a queen and her beloved companion.